An Idea Conquers the World: Reflections of the 20th Century European Idea in the European Discourse of the 21st Century - Sakalauskaitė, Monika (Vilnius University Open Series, 2025)
In the context of ongoing military conflicts in Europe and globally, the question of Europe’s identity has assumed heightened relevance. The idea of Europe has undergone significant transformations, in terms of its geographical and ethnic boundaries. These transformations have also affected the way in which Europe is thought about. From the second half of the 20th century onwards, the subject has been superseded by the search for (an) identity, thus the concept of Europe as an idea ceased to be a subject of interest. It is currently a political and economic entity attempting to navigate the numerous identities that exist within it. This paper analyses how the ideas of the 20th century, which emerged in the search for a solution to the European identity crisis that hit the continent after the First World War, are reflected in the European discourse of the 21st century. To this end, the paper examines the emergence and evolution of the Pan-European project into political entities. It also explores the ways of resolving the crisis of the European identity from religious and sociological perspectives, and proposes a new perspective on the future of Europe.
Keywords: Europe; idea of Europe; identity; crisis of the mind; religion; society; radical imagination